Analisa Sistem Informasi Manajemen Sumber Daya Manusia Pada Proses Rekrutmen, Demosi dan Mutasi di PT. Yasunli Abadi Utama Plastik - Soleh, Oleh; Hidayat, Wahyu; Rustanti S, Fitri Widya (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2019)
It takes A good system is needed to monitor all activities, productivity, discipline and career path of employees in a developing company, because the current conditions are all done manually. This can cause errors in making decisions for these employees. To facilitate the company in making decisions and actions against these employees, we need a system that can make a summary of the results of employee performance in terms of activity, productivity, discipline and career path. This needs to be analyzed in the Human Resources (HR) system or more commonly known as Human Resource and for the analytical method used today uses three methods, observation, literature and analysis. The object used in this problem is PT. Yasunli Abadi Utama Plastik. The target of achievement in this case is to take action and make decisions against high achieving or quick-achieving employees. Keywords: System, Human Resources, Human Resource, Yasunli Abadi Utama Plastik.